先化简再求值(x^2/x-1-x+1)/4x^2-4x+1/1-x,其中x^2=1
1个回答
=(x²-x²+x+x-1)/(x-1)×(1-x)/(2x-1)²
=(2x-1)/(x-1)×[-(x-1)/(2x-1)²]
=-1/(2x-1)
=1/(1-2x)
相关问题
先化简再求值先化简再求值:(x-x/x+1)(x+1/x^2+4x+4)(x^2-4/x^2-2x),其中x=-0.5
先化简,再求值:4x(x+1)-(2x+1)(2x-1),其中x=-2\1
先化简,再求值:(x−1x2−1+1x+1)÷4x2+x,其中x=-2.
{2x+3}{x-1}-{2x+1}2+4x{x+1} ,其中x=-2 {先化简,再求值}
先化简,再求值:4(x+1) 2 -7(x-1)(x+1)+3(1-x) 2 ,其中x=- 。
先化简,再求值:(x2x−2−4x−2)×1x2+2x,其中x=[1/4].
先化简再求值":4x(x-1)-(2x+3)(2x-3),其中x=-1
先化简,再求值:(-2x)*(3x²-4x-1)+6x³-2x,其中x²=1
(2011•福建)(1)先化简,再求值:x(4-x)+(x+1)(x-1),其中x=[1/2].
先化简,再求值:[x/x+1−x+3x+1•x2−2x+1x2+4x+3],其中x=1.